Postmenopausal women's experiences of weight maintenance following a very low energy diet - Claudia Harper; Judith Maher; Michelle Hsu; Anne Grunseit; Radhika Seimon; Amanda Sainsbury (Obesity Science & Practice, 2023)
Abstract Introduction Very low energy diets (VLEDs) effectively induce substantial weight loss in people with obesity, yet they are rarely used as a first line treatment. There is a belief that such diets do not teach the lifestyle behavior changes needed for long‐term weight maintenance. However, little is known about the lived experiences of people who have lost weight on a VLED in the long term. Methods This study aimed to explore the behaviors and experiences of postmenopausal women who had followed a 4‐month VLED (using total meal replacement products [MRPs]), followed by a food‐based, moderately energy‐restricted diet for an additional 8 months, as part of the TEMPO Diet Trial. Qualitative in‐depth semi‐structured interviews were conducted with 15 participants at 12 or 24 months (i.e., at 8 or 20 months post diet completion). Transcribed interviews were analyzed thematically using an inductive approach. Results Undertaking a VLED was reported by participants to confer advantages in weight maintenance that previous weight loss attempts had not been able to do for them. Firstly, the rapid and significant weight loss, in conjunction with ease of use, was motivational and helped instill confidence in the participants. Secondly, the cessation of a normal diet during the VLED was reported by participants to break weight gain‐inducing habits, allowing them to abandon unhelpful habits and to introduce in their place more appropriate attitudes toward weight maintenance. Lastly, the new identity, helpful habits and increased self‐efficacy around weight loss supported participants during weight maintenance. Additionally, participants reported that ongoing occasional use of MRPs provided a useful and easy new strategy for countering weight regain and supporting their weight maintenance regimen. Conclusion Among the participants in this qualitative study, most of whom had maintained a loss of over 10% of their baseline body weight at the time of interview, using a VLED in the context of a clinical weight loss trial conferred confidence, motivation and skills for weight maintenance. These findings indicate that VLEDs with clinical support could be successfully leveraged to set up behaviors that will support weight maintenance in the long term.